EFEK IMUNOMODULATOR EKSTRAK DAUN ASAM JAWA (Tamarindus indica L) TERHADAP JUMLAH DAN JENIS SEL LEUKOSIT PADA MENCIT BALB/C YANG DIINFEKSI BAKTERI Salmonella Typhi - mala aulia hapsari; Meka Faizal Farabi (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Typhoid fever is an acute infectious disease caused by Salmonella typhi germs, mainly affecting the digestive tract with symptoms of fever for more than 7 days. In Indonesia alone, the incidence rate for this disease is estimated to be around 300-810 cases per 100,00 population per year. Tamarind leaves with flavonoid content can inhibit anti-inflammatory activity. This study aims to determine the immunomodulatory effect of tamarind leaf extract (Tamarindus indica L). Against the number and type of leukocyte cells in balb/c mice infected with Salmonella typhi bacteria. In this study using the experimental group method of Balb/c male mice. Pure form (Tamarindus indica L.) shows immunomodulatory activity such as an increase in the number and type of leukocytes. The research sample was 25 Balb/c male mice weighing 20-30 grams which were then divided into 5 treatment groups. The dose variation is 50 mg/kg BW, 75 mg/kg BW, and 100 mg/kg BW orally for 6 days. Then on day 7 was infected using Salmonella typhi bacteria. Statistical test results showed that the dose groups of 50, 75, and 100 mg/kg BW were not significantly different from the negative control (p>0.05).